2017
DOI: 10.3174/ajnr.a5348
|View full text |Cite
|
Sign up to set email alerts
|

[18F]-Sodium Fluoride PET MR–Based Localization and Quantification of Bone Turnover as a Biomarker for Facet Joint–Induced Disability

Abstract: To prospectively evaluate the relationship between low back pain-related disability and quantitative measures from dynamic sodium fluoride (18F-NaF) PET-MRI. Six patients with facetogenic low back pain underwent dynamic 18F-NaF PET/MRI. PET metrics were correlated with clinical measures and MRI grading of lumbar facet arthropathy. Significant positive correlation was observed between maximum FJ uptake rate and clinical disability (p < 0.05). These data suggest dynamic 18F-NaF PET may serve as a useful biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…For more complicated modeling using the Hawkins method, there is a plethora of commercial and noncommercial software, for example, MATLAB (The MathWorks, Inc., Natick, Massachusetts, USA), PMOD (PMOD Technologies Ltd., Zurich, Switzerland), Hermes Medical Solutions (Hermes Medical Solutions Ltd, Stockholm, Sweden), APPIAN, 72 QMODELING, 73 KINFITR, 74 AMIDE, 75 CARIMAS, 76 COMKAT, 77 KMTOOL, 78 or TKMF. 79 We hope that other new emerging clinical applications of [ 18 F] NaF PET [80][81][82][83][84][85][86][87] may also benefit from this review, especially from the SP-AIF model presented in Equation 3.…”
Section: Calculation Of K I Valuesmentioning
confidence: 99%
“…For more complicated modeling using the Hawkins method, there is a plethora of commercial and noncommercial software, for example, MATLAB (The MathWorks, Inc., Natick, Massachusetts, USA), PMOD (PMOD Technologies Ltd., Zurich, Switzerland), Hermes Medical Solutions (Hermes Medical Solutions Ltd, Stockholm, Sweden), APPIAN, 72 QMODELING, 73 KINFITR, 74 AMIDE, 75 CARIMAS, 76 COMKAT, 77 KMTOOL, 78 or TKMF. 79 We hope that other new emerging clinical applications of [ 18 F] NaF PET [80][81][82][83][84][85][86][87] may also benefit from this review, especially from the SP-AIF model presented in Equation 3.…”
Section: Calculation Of K I Valuesmentioning
confidence: 99%
“…Not only does NaF-PET/CT facilitate the diagnosis of pars stress but it can also help diagnose other potential causes of back pain, such as facet arthropathy. [80][81][82] The observation that NaF uptake at the cervical, thoracic, and lumbar spine is associated with increased body weight in healthy individuals suggests that NaF-PET/CT can detect early changes in the spine related to degeneration. 83 In 42 adult patients with back pain and no history of spine surgery, NaF-PET/CT scans identified the cause of pain in 37 (88%) of the patients.…”
Section: Back Painmentioning
confidence: 99%
“…82 Furthermore, NaF activity at lumbar facet joints has been found to correlate with both MR findings and clinical disability. 80 Mabray and colleagues 81 observed that, in 30 adult patients who underwent imaging by NaF-PET/CT, uptake of NaF was only weakly correlated with CT Pathria grade of facet osteoarthropathy. Thereby, the investigators reasoned that the assessment of bone turnover with NaF provided new information that can be used to supplement structural data provided by CT.…”
Section: Back Painmentioning
confidence: 99%
“…36,40 Additionally, increased F 18 -NaF uptake was shown to correlate well with those patients with facet joint pain. [41][42][43] Further, significantly increased F 18 -NaF PET subchondral bone uptake was observed in a patient population at risk for developing degenerative joint disease. 44 These findings support the hypothesis that increased metabolic bone activity detected with F 18 -NaF PET can serve as a marker for early bone remodeling in OA.…”
Section: F 18 -Sodium Fluoride Pet/mri For Osteoarthritismentioning
confidence: 99%